PENGARUH UKURAN KANTOR AKUNTAN PUBLIK,KEBERADAAN ANAK PERUSAHAAN, DAN DEWAN KOMISARIS INDEPENDEN TERHADAP AUDIT FEES PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Savira Arvianti Putri, - (2019)
This paper aims to determine the effect of audit firm size, subsidiaries and independent commissioner on audit fees on all manufacture companies listed in Indonesia Stock Exchange period 2015-2017. The sampling in this study of 93 manufacture companies listed in Indonesia Stock Exchange period 2015-2017 with purposive sampling method. The number of samples was obtained from 93 companies with total 279 sample. After eliminating the outlier data, which eventually resulted 175 observations that ready to be analyzed and tested. The paper builds on cross section data. This paper uses multiple linear regression with some help of programming data using SPSS (Statistical Product and Service Solution) 25th. The findimg reveals that Audit Firm Size and subsidiaries have an influence on Audit fees. However, independent commissioner have no effect on audit fees